Peculiarities of some immunity indicators in patients with nonproliferative forms of chronic glomerulonephritis and nephrotic syndrome - V. Driianska; M. M. Velychko; O. Petrina; T. Poroshina; V. Nepomnyaschiy; L. Liksunova; N. Malashevska (Ukrainian Journal of Nephrology and Dialysis, 2018)
The aimof our work was to determine the peculiarities of human leukocyte antigen (HLA) cytokines and factors of endothelial dysfunction in the blood of patients with nonproliferative forms (NP) of chronic glomerulonephritis (CGN) and nephrotic syndrome (NS).Methods. The distribution of HLA-antigens by identification of lymphocytes using of the common microlymphocyte toxic test (Terasaki) was studied in 264 patients with CGN, NS and 350 healthy donors. Among the examined patients were 96 subjects with MP GN. The diagnosis was confirmed morphologically using the thin needle nephrobiopsy. The immuno-enzymic method ELISA was used to study the levels of cytokines and the factors of endothelial dysfunction in blood of 110 patients. Results. We obtained a high relative risk (RR > 2) for CGN, NS at the presence of HLA-A23, 24, 28, B8, 38, 41, 44 in phenotype (for NP + А30), the causal role in etiopathology (σ>0.1) is indicated for A24, 28; B8 (NP +A19+31+32). The disease protectors are B12 and B16 (NP +A9. The association of some antigens with development of various morphologic forms of GN was determined. Moreover, we found a statistically high levels of pro-inflammatory cytokines (tumor necrosis factor-α (TNF-α), IL-17, monocyte chemoattractant protein 1 (MCP-1)), anti-inflammatory cytokines (IL-4, transforming growth factor β) and factors of endothelial dysfunction (vascular endothelial growth factor (VEGF), soluble vascular cell adhesion molecule-1) in the patients with NP GN compared to healthy donors. The MCP-1 levels in the patients with proliferative GN are reliably higher than in NP patients.No statistically significant dynamics of cytokines level in the patients with NP GN was revealed (exclude the level of TNF-α) after the treatment. But, the positive treatment effect was associated with the statistically decreased of TNF-α, MCP-1 and VEGF. Our results suggest that HLA-antigens and other indicators of immunity (TNF α, MCP-1 and VEGF) can be used as the additional prognostic markers in the patients with GN and NS.